Population Pharmacokinetics of Glecaprevir/Pibrentasvir in HCV-infected Japanese Subjects in Phase 3 CERTAIN-1 and CERTAIN-2 Trials - Suleiman, Ahmed Abbas; Lin, Chih-Wei; Liu, Wei; Eckert, Doerthe; Mensing, Sven; Burroughs, Margaret; Kato, Koji; Chayama, Kazuaki; Kumada, Hiromitsu; Oberoi, Rajneet K (Journal of clinical pharmacology, 2020)
Glecaprevir (GLE)/pibrentasvir (PIB) 300 mg/120 mg once daily (Mavyret/Maviret) is an all-oral, pangenotypic, interferon- and ribavirin-free combination regimen approved for the treatment of chronic hepatitis C virus (HCV) infection. The objective of the current analyses was to characterize the pharmacokinetics (PK) of GLE/PIB in HCV-infected Japanese patients. Data from 332 subjects enrolled in 2 Japan phase 3 trials, CERTAIN-1 and CERTAIN-2, were used in the analyses. Pharmacokinetics of GLE/PIB were characterized using a nonlinear mixed-effects modeling. The analyses evaluated the impact of covariates (concomitant medications and demographic and clinical covariates such as renal impairment, effect of cirrhotic status) on GLE/PIB PK. GLE and PIB PK were described by 1- and 2-compartment models, respectively. Presence of cirrhosis, age, and body weight were identified as significant covariates on GLE/PIB PK. A trend toward higher GLE and PIB exposures in older patients and higher PIB exposures in heavier patients was observed; however, these increases were not considered clinically meaningful. GLE and PIB exposures were higher in HCV-infected subjects with cirrhosis (Child-Pugh A; GLE area under the plasma concentration-time curve was 160% higher, and PIB area under the plasma concentration-time curve was 21% higher) compared to subjects without cirrhosis. Renal function (including subjects with end-stage renal disease with dialysis) had no impact on GLE or PIB exposures. The GLE/PIB dose was well tolerated in the Japanese population, and no dose adjustment is needed for the evaluated intrinsic and extrinsic factors.